Kajian Kuantiitas Mata Air Desa Sambirata Kecamatan Cilongok Kabupaten Banyumas - Arif Ihsanul Fikri; Suwarsito Suwarsito; Esti Sarjanti (UM Purwokerto Press, 2022)
Water is an absolute necessity for human life, there is no perfect life and it takes place without water, the water used to meet the needs of human life comes from various sources in the form of rainwater, surface water and groundwater, one of which can be obtained from the springs, which is the emergence of groundwater to the surface, in Sambirata Village, Cilongok District, Banyumas Regency is a village that has a source of spring water that is utilized and used for the needs of the community in the form of PAMSIMAS and affected by the construction of the Geothermal Power Plant (PLTPB) in 2017 which is on the north side of the border with Brebes Regency. The purpose of this study is to determine the condition of the quantity of 3 eyes in Sambirata because these 3 eyes are used by the community to fulfill daily life. The method used in this study is observation in the field in the form of measuring the discharge of the spring, determining the location of the coordinates of 3 subjects, as well as processing secondary data to determine factors that affect the quantity of the spring. The three springs can be classified in perennial springs, based on their discharge tends to be the discharge class according to Meinzer including class VI (0.1 - 1liter/second) both in the dry season and the rainy season.